# Binet Form/First Form

## Theorem

Let $m \in \R$.

Define:

 $\ds \Delta$ $=$ $\ds \sqrt {m^2 + 4}$ $\ds \alpha$ $=$ $\ds \frac {m + \Delta} 2$ $\ds \beta$ $=$ $\ds \frac {m - \Delta} 2$
$U_n = m U_{n - 1} + U_{n - 2}$

where:

 $\ds U_0$ $=$ $\ds 0$ $\ds U_1$ $=$ $\ds 1$

has the closed-form solution:

$U_n = \dfrac {\alpha^n - \beta^n} \Delta$

## Proof

Proof by induction:

Let $\map P n$ be the proposition:

$U_n = \dfrac {\alpha^n - \beta^n} \Delta$

### Basis for the Induction

We have:

 $\ds \frac {\alpha^0 - \beta^0} \Delta$ $=$ $\ds \frac {1 - 1} \Delta$ Zeroth Power of Real Number equals One $\ds$ $=$ $\ds 0$ $\ds$ $=$ $\ds U_0$ From definition $\ds \frac {\alpha^1 - \beta^1} \Delta$ $=$ $\ds \frac 1 \Delta \paren {\frac {m + \Delta} 2 - \frac {m - \Delta} 2}$ $\ds$ $=$ $\ds \frac 1 \Delta \paren \Delta$ $\ds$ $=$ $\ds 1$ $\ds$ $=$ $\ds U_1$ From definition

Therefore $\map P 0$ and $\map P 1$ are true.

This is the basis for the induction.

### Induction Hypothesis

This is our induction hypothesis:

For some $k \in \N$, both $\map P k$ and $\map P {k + 1}$ are true.

That is:

$U_k = \dfrac {\alpha^k - \beta^k} \Delta$
$U_{k + 1} = \dfrac {\alpha^{k + 1} - \beta^{k + 1}} \Delta$

Now we need to show true for $n = k + 2$:

$\map P {k + 2}$ is true.

That is:

$U_{k + 2} = \dfrac {\alpha^{k + 2} - \beta^{k + 2}} \Delta$

### Induction Step

This is our induction step:

First we notice that:

 $\ds \alpha^2$ $=$ $\ds \paren {\frac {m + \Delta} 2}^2$ $\ds$ $=$ $\ds \frac 1 4 \paren {m^2 + 2 m \Delta + m^2 + 4}$ Square of Sum $\ds$ $=$ $\ds \frac 1 4 \paren {2 m^2 + 2 m \Delta + 4}$ $\ds$ $=$ $\ds \frac {m^2 + m \Delta} 2 + 1$ $\ds$ $=$ $\ds m \alpha + 1$

Similarly:

 $\ds \beta^2$ $=$ $\ds \paren {\frac {m - \Delta} 2}^2$ $\ds$ $=$ $\ds \frac 1 4 \paren {m^2 - 2 m \Delta + m^2 + 4}$ Square of Sum $\ds$ $=$ $\ds \frac 1 4 \paren {2 m^2 - 2 m \Delta + 4}$ $\ds$ $=$ $\ds \frac {m^2 - m \Delta} 2 + 1$ $\ds$ $=$ $\ds m \beta + 1$

Thus:

 $\ds U_{k + 2}$ $=$ $\ds m U_{k + 1} + U_k$ Definition of the recursive sequence $\ds$ $=$ $\ds m \paren {\frac {\alpha^{k + 1} - \beta^{k + 1} } \Delta} + \frac {\alpha^k - \beta^k} \Delta$ Induction Hypothesis $\ds$ $=$ $\ds \frac 1 \Delta \paren {\paren {m \alpha + 1} \alpha^k - \paren {m \beta + 1} \beta^k}$ $\ds$ $=$ $\ds \frac 1 \Delta \paren {\alpha^2 \alpha^k - \beta^2 \beta^k}$ From above $\ds$ $=$ $\ds \frac {\alpha^{k + 2} - \beta^{k + 2} } \Delta$

This show that $\map P {k + 2}$ is true.

By principle of mathematical induction, $\map P n$ is true for all $n \in \N$.

$\blacksquare$